Effects of stannum (Sn) addition on corrosion behavior and biocompatibility in vitro of biodegradable Zn–Sn alloys. Issue 2 (15th September 2021) - Guo, Pushan; Bagheri, Robabeh; Yang, Lijing; Song, Zhenlun; Liu, Yaxuan
Abstract: Zinc (Zn) and its alloys, as novel biodegradable metals, hold great potential in bone implant and metallic stents. Stannum (Sn), an essential trace element, plays an important role in maintaining life activities. Herein, Sn is selected as an alloying element to be added into the Zn matrix to explore the possibility of Zn–Sn alloy as a biodegradable metal for clinical application. This article systemically studies the effects of Sn content on microstructural, electrochemical behavior, corrosion rate, and in vitro biocompatibility of Zn–Sn alloys. Results indicate that the Sn‐rich phase is the main form of Sn in the as‐extruded alloys, and the solid solubility is in an extremely minute quantity. The corrosion of Zn–Sn alloys in conventional simulated body fluid (c‐SBF) solution shows apparent electrochemical characteristics, and Sn‐rich phases are corroded preferably. The corrosion rates of Zn–1.0Sn and Zn–2.0Sn are under 0.2 mm year −1, which can satisfy the requirement of biodegradable medical materials. In addition, Zn–1.0Sn exhibits much better cytocompatibility and hemocompatibility than Zn–2.0Sn. Therefore, Zn–Sn alloy shows great potential applications in the biological field and can be further studied and developed. Abstract : Zn–Sn alloys are composed of the main phase and Sn‐rich phase, which is the admixture of Zn and Sn. The corrosion in the conventional simulated body fluid (c‐SBF) solution showed apparent electrochemical characteristics, and Sn‐rich phases were corroded preferably. Zn–1.0Sn exhibited a low initial corrosion rate, which resulted in better biocompatibility and hemocompatibility. In general, Sn can be regarded as a candidate alloying element added to the Zn matrix, but the content should not be excessive.